Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI - Wigati, Kimara Ugi; Aprica Isabella, Astrid; Sekar Sari, Meita (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this study was to determine the effect of profitability and company size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the food and beverage sub-sector for the period 2020-2022. This study uses quantitative research methods with multiple linear regression analysis approaches. The data used in this research is secondary data obtained from the financial statements of food and beverage companies in 2020-2022. The results showed that profitability and company size partially had a positive and significant effect on firm value. Meanwhile, profitability and company size simultaneously have a significant effect on firm value.